Modelling Study on Evaporative Freezing Process of Water Droplet in Artificial Snowmaking - G. El Achkar; B. Liu; R. Bennacer (New Trends in Physical Science Research Vol. 1, 2022)
In this paper, a modelling study on evaporative freezing process of water droplet was conducted in order to better understand the artificial snowmaking and hence to optimise its machine design. To this end, mass and heat transfer theoretical models of a single water droplet cooling in an air space were established and implemented in a numerical model developed using the software COMSOL Multiphysics. The effects of the air temperature, relative humidity and velocity and the water droplet initial diameter and temperature on this process were identified and analysed, and their appropriate ranges for the snowmaking were determined.